2018
DOI: 10.1039/c8tc00530c
|View full text |Cite
|
Sign up to set email alerts
|

Electric-double-layer transistors for synaptic devices and neuromorphic systems

Abstract: This article reviews the recent progress in the field of electric-double-layer transistors for synaptic devices and neuromorphic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
187
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 211 publications
1
187
0
1
Order By: Relevance
“…As a final demonstration of the utility of this field‐driven oxygen vacancy generation approach, neuromorphic transistors with programmable plasticity were realized in a comprehensive manner, correlating the above explanations with weight plasticity. Very recently, electrolyte‐gated FETs have been extensively researched for hardware emulation of biological signal‐processing . Contrary to mass storage and conventional logic operations, emulation of biological signal processing sets unique requirements on the hardware switching devices, namely a strong operational history, analog (nonabrupt) switching transitions, continuously distributed conductance states, and programmable plasticity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final demonstration of the utility of this field‐driven oxygen vacancy generation approach, neuromorphic transistors with programmable plasticity were realized in a comprehensive manner, correlating the above explanations with weight plasticity. Very recently, electrolyte‐gated FETs have been extensively researched for hardware emulation of biological signal‐processing . Contrary to mass storage and conventional logic operations, emulation of biological signal processing sets unique requirements on the hardware switching devices, namely a strong operational history, analog (nonabrupt) switching transitions, continuously distributed conductance states, and programmable plasticity .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, electrolyte-gated FETs have been extensively researched for hardware emulation of biological signalprocessing. [34,35] Contrary to mass storage and conventional logic operations, emulation of biological signal processing sets unique requirements on the hardware switching devices, namely a strong operational history, analog (nonabrupt) switching transitions, continuously distributed conductance states, and programmable plasticity. [36] Although two-terminal memristive solutions have dominated this research area, threeterminal FET-based solutions have recently received significant scientific attention in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the neuromorphic computing systemsbased multiple value RRAM devices are expected to overcome the shortcomings of the von Neumann architecture computing platforms and provide high efficiency for data centric applications in the big data era. [3,58,128,133,[146][147][148][149][150] Calcium ions (Ca 2þ ) play a crucial role in the transmission of information between the presynaptic and postsynaptic membrane of biological synapses. Researchers have found that the accumulation and diffusion of silver ions (Ag þ ) in the RRAM functional layer might simulate this passing process of biological information under the pulse sweeping voltages.…”
Section: Application Prospectsmentioning
confidence: 99%
“…Finally, the neuronal network will interpret the visual information so that we can perceive what we see. In the neural network, synapses act as a basic unit to transmit, memorize, recognize, and learn the visual information [4][5][6][7] . Visual perception is the main channel for humans to obtain information.…”
Section: Introductionmentioning
confidence: 99%